The Black Death in the Middle East - Dols, Michael W. (Michael Walters), 1942- (Book collections on Project MUSE., 2019)
In this book the author uses primarily Arabic sources to discuss the transmission of the Black Death to the Middle East and the devastation the disease caused on the society and economics in Egypt and Syria.